A Case Report of Tetralogy of Fallot Associated with Tight Lesion of the Left Anterior Descending Coronary Artery - Kabir, J; Rima, R; Hassan, R; Badruddoza, AMM; Khatoon, S (Cardiovascular Journal, 2012)
A small subset of patients with TOF present later in life with unsuspected or untreated disease. Tetralogy of Fallot in adults represents a special group with peculiar problems related to the effects of prolonged cyanosis over the heart and other organs .Older age has been considered as incremented risk factor for surgical mortality and long-term survival in patients with TOF. Based on this assumption, indication for surgery after long-standing cyanosis has caused controversy. There are few reports that studied this issue have proved some benefit in repairing adults with TOF .The greatest benefit of complete repair at this age is the functional improvement. We report a male patient with TOF with tight lesion of the left anterior descending coronary artery diagnosed at age 40 years and successfully underwent total correction along with CABG. This patient was the oldest documented in Bangladesh undergoing successful corrective surgery for TOF with CABG. Keywords: Tetralogy of Fallot; Left anterior descending artery (LAD); CABG. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9396 Cardiovasc. J. 2011; 4(1): 88-91